Tailored message interventions versus typical messages for increasing participation in colorectal cancer screening among a non-adherent population: A randomized controlled trial - Kei Hirai; Yoshiki Ishikawa; Jun Fukuyoshi; Akio Yonekura; Kazuhiro Harada; Daisuke Shibuya; Seiichiro Yamamoto; Yuri Mizota; Chisato Hamashima; Hiroshi Saito (BMC, 2016)
Abstract Background The purpose of this study was to examine the effectiveness and cost-efficiency of a tailored message intervention compared with a non-tailored message intervention for increasing colorectal cancer (CRC) screening rates among a non-adherent population, in a community-based client reminder program. Methods After a baseline survey for psychological segmentation, 2140 eligible individuals were randomly assigned either to a group with a tailored matched-message condition (N = 356), a group with a non-tailored unmatched-message condition (N = 355), or to two control groups, one using a typical message with a professional design (N = 717) and one without a professional design (N = 712). The main outcome measure was attendance rates in a community-organized CRC screening program within five months of receiving a print reminder. Results There was a significant difference in fecal occult blood test (FOBT) attendance rates at follow-up assessments between the tailored matched-message condition (14.0 %) and the control (9.9 %; OR = 1.48, p = 0.026), while there was no significant difference between the unmatched-message condition (11.0 %) and the control (OR = 1.12, p = 0.558), and between the matched-message condition and the unmatched-message condition (OR = 1.32, p = 0.219). The cost of a one-person increase in FOBT screening was 3,740 JPY for the tailored matched-message condition, while it was 2,747 JPY for the control. Conclusions A tailored-message intervention for segmented individuals designed to increase CRC screening rates in a community-based client reminder program was significantly effective compared to a usual reminder, but not more effective than an unmatched message in a randomized controlled trial, and was not sufficiently effective to highlight its value from a cost perspective. Therefore, the tailored intervention including target segmentation needs to be improved for future implementation in a CRC screening program for a non-adherent population. Trial registration UMIN Clinical Trials Registry UMIN000004384 . Date of Registration: March 2011.